2020
DOI: 10.3389/fpubh.2020.00278
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Safety and Hormesis

Abstract: The statements presented in this publication are solely the responsibility of the author. Conflict of Interest:The author declares that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…Although this theory is applied to ionizing radiation, it also suggests that low doses of radiation may exert protective effects and induce beneficial outcomes. In contrast, higher doses lead to detrimental effects (Jargin, 2020). Delavarifar et al (2020) observed a similar discovery of beneficial low-dose radiation generated by Wi-Fi routers.…”
Section: The Effect Of Wi-fi Exposure On Male Children Reproductive S...mentioning
confidence: 84%
See 1 more Smart Citation
“…Although this theory is applied to ionizing radiation, it also suggests that low doses of radiation may exert protective effects and induce beneficial outcomes. In contrast, higher doses lead to detrimental effects (Jargin, 2020). Delavarifar et al (2020) observed a similar discovery of beneficial low-dose radiation generated by Wi-Fi routers.…”
Section: The Effect Of Wi-fi Exposure On Male Children Reproductive S...mentioning
confidence: 84%
“…Although this theory is applied to ionizing radiation, it also suggests that low doses of radiation may exert protective effects and induce beneficial outcomes. In contrast, higher doses lead to detrimental effects ( Jargin, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, other dose-response models, including the threshold and hormesis models, propose alternative relationships. The threshold model posits the existence of a dose below which no detrimental effects are expected, implying a dose 'safety zone', offering a stark contrast to the LNT model [ 27 ]. The hormesis model, on the other hand, suggests that low levels of radiation might confer a protective effect.…”
Section: Reviewmentioning
confidence: 99%
“…There can be also unknown bias and confounders, the more so as there are motives to strangulate atomic energy fuelled by interests of fossil fuel producers. Reliability of certain studies, including some of those referenced by Wakeford (2021), has been questioned previously (Jargin 2010(Jargin , 2020(Jargin , 2021. Reported dose-effect correlations may be caused or influenced by dose-dependent selection and self-selection noticed in various exposed cohorts (McGeoghegan et al 2008, Zablotska et al 2013.…”
Section: Dear Sirmentioning
confidence: 99%